Conversational Maxims Used by BTS Members - Anggraini, Nessa Aqila (Lingual Journal of Language and Culture; Vol 13 No 1 (2022): Lingual: Journal of Language and CultureDO - 10.24843/LJLC.2022.v13.i01.p05, 2022)
The goal of the conversation process is to convey information and the understanding of that information smoothly. In order to achieve that, both of the speaker and listener are expected to use language effectively. This research aims at analyses the use of conversational maxims of the BTS members’ utterances in the BTS Run reality show by using Grice’s theory of cooperative principle. The objectives of this research are to find out the types of conversational maxims used by BTS on the BTS Run reality show with Cooperative Principal theory. Qualitative is applied as the research method in this research. The data are the utterances of BTS members in the BTS Run reality show that contains implied meaning. The result of this research shows that the members of BTS often violate the maxim of quantity over other maxims. Keywords: conversational, maxims, cooperative principle, BTS